A literature survey of the operation optimization in chip shooter placement machines - (:unkn) unknown (My University, 2009)
Computer controlled electronic component placement machines have become major resources in electronic equipment manufacturers. They brought speed and reliability to the assembly operations. However, these machines are quite expensive and efficient use of them is essential. Unfortunately finding out the efficient way of using them mostly leads to complex operations research problems. In this study we undertake a type of placement machines which perhaps leads the most complicated problems. These are the chip shooter machines and recently they became very popular in the industry. We survey the studies made regarding these machines; state the level of complexity undertaken, the solution algorithms suggested and the results obtained. In doing so we aimed to provide a comprehensive survey and a starting reference for those who are interested in optimizing these machines. The research areas that are open to further improvement are also indicated. © 2009 PICMET.